Studying additive effects of combining rTMS with cognitive control training: a pilot investigation - Dalhuisen, Iris; Schutte, Céline; Bramson, Bob; Roelofs, Karin; Eijndhoven, Philip van; Tendolkar, Indira (Frontiers in Human Neuroscience, 2023)
Background: Repetitive transcranial magnetic stimulation (rTMS) on the dorsolateral prefrontal cortex (DLPFC) is an effective treatment for depression, that has been proposed to work via enhancement of cognitive control. Cognitive control training (CCT) can also alleviate depression by relying on DLPFC activation. As the additive effects of rTMS and CCT are unclear we set out to conduct a within-subject pilot study in healthy controls. Methods: Seventeen participants received two sessions of individualized resting-state connectivity-guided high-frequency rTMS, whilst randomly performing CCT or a control task. After each session, a negative mood was induced. Results: We found effects on mood and cognitive control after rTMS + CCT as well as rTMS + control, which were indiscriminative between conditions. Given the moderate evidence for the absence of an effect these results provide sufficient ground to not perform a full study. Conclusions: Our results demonstrate no differential effects of single sessions combining rTMS and CCT in a healthy population, even with the methodological improvement of individualized neuronavigation. The improvement in cognitive control seen in both conditions could indicate that a simple cognitive task is sufficient when studying additive rTMS effects. Future studies should focus on augmenting effects of various cognitive tasks, and compare the present interventions with rTMS or cognitive task alone.